Factors influencing voluntary premarital medical examination in Zhejiang province, China: a culturally-tailored health behavioral model analysis - Gu, Yaming; Li, Lu; Zhou, Chi; Yang, Tingzhong; Dong, Hengjin (BMC public health, 2014)
Premarital medical examination (PME) compliance rate has dropped drastically since it became voluntary in China in 2003. This study aimed to establish a prediction model to be a theoretic framework for analyzing factors affecting PME compliance in Zhejiang province, China.